The issue of quality of higher education in Russia - Anna. A Gnutova; Sergei. A Nechitaylo (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In conditions of growing competition in the education market success can only count universities providing education of the highest quality. The modern world is radically changing consumer attitudes to higher education, forcing the change and the very system of higher education. The quality of educational services becomes a guarantee of the attractiveness of the university and the credibility of the consumers.This article discusses some aspects of the basic problems of higher education in Russia. Attention is paid to the problems of the quality of education, the small percentage of employment of professors and teaching staff of higher education in science, theproblem of a large number of universities in the number of population, the issue of remuneration of teachers and others.